Legal Review Of Decision Number 21-K/Pmt/Ii/Ad/Ii2022 Reviewed From The Competence Of Adjudicating Military Courts In The Case Of Corruption Connectivity Of Army Compulsory Housing Savings - Pratama, Harits Surya; Z, Yenny Fitri (UNIVERSITAS PAKUAN, 2025)
Abstract Connection A Connection Case is a form of law enforcement involving both civilian and military actors in the same crime, which is regulated through a special mechanism in the Indonesian legal system. This study examines Decision Number 21-K/PMT-II/AD/II/2022, which relates to the corruption case of the Army's Mandatory Housing Savings Fund (TWP AD). This study analyzes the legal basis, chronology, and reasons for the case being tried in military court, despite the involvement of civilians, as well as the role of the Deputy Attorney General for Military Crimes (JAMPIDMIL) in handling it. The method used is a normative juridical approach with an analysis of court decisions. The results of the study also show that the mechanism in this connection case is not fully in line with the objectives of Law Number 31 of 1997 concerning Military Justice, thus raising questions regarding the effectiveness of just law enforcement. Keywords: Connectivity, Justice System, Military Corruptions